Elisée Reclus and Elie Reclus in memoriam. Including: tributes, appreciations and essays by Elie Faure, Albert Heim, [a.o.]. Fragments, letters, and over sixty woodcuts by Louis Moreau. Compiled, ed. and printed by Joseph Ishill (The Oriole Pr., 1927)
Bibl.